Pengaruh Profitabilitas dan Net Profit Margin terhadap Harga Saham Perusahaan Manufaktur - Fora Susanti; Anisa Sains Kharisma; Titi Rahmawati; Nasiruddin; Roni (Universitas Muhadi Setiabudi, 2021)
Recently, Indonesian people are very interested in stocks as a form of investment. Stock investment was chosen because it can generate large returns in a short time or short returns in one day. Most of the returns obtained come from the increase or decrease in stock prices from one time to another. The purpose of this study is to determine and assess the effect of profitability metrics (ROA and ROE) and net profit margin, either individually or together, on stock prices. To ensure the relationship between the independent variable and the dependent variable, the researcher used an associative causal approach. 15 (fifteen) manufacturing companies in the foodsand beverage sub-sector for the year 2019–2020 listed on the IDX are the population of this study. According to the analysis findings, NPM has a considerable impact on the share price alone, while profitability has a smaller impact. The results of the F test simultaneously show that the three variables have no significant effect on stock prices.